Praktik pemberian MPASI (Ketepatan, Jenis, Tekstur dan Frekuensi) pada anak stunting usia 6-24 bulan di Kabupaten Natuna: Studi kualitatif - Mumtaz, Hammada Hanifia; Aji, Arif Sabta; Nabiella, AD; Nurlita, Safira; Hidayati, Misna; Aprilia, Veriani; Afifah, Effatul (UHAMKA PRESS, 2025)
Stunting is a growth failure in children under five years old due to chronic malnutrition, particularly during the first 1,000 days. This condition is generally caused by low nutritional intake and recurrent infections. It can be caused by inadequate complementary feeding. This study aimed to determine the complementary feeding practices (accuracy, type, texture, and frequency) among stunted children aged 6-24 months. This qualitative study design used a phenomenological approach with purposive non-probability sampling and was conducted in September-October 2024. Main informants were 18 mothers of children aged 6–24 months (both stunted and non-stunted), while key informants included a nutritionist and the head of the public health center in Serasan and Serasan Timur. Data were collected through Focus Group Discussion (FGD) and in-depth interviews. Data analysis was conducted thematically using NVivo 12.0. The provision of complementary foods to stunted children shows a discrepancy in timeliness with applicable recommendations. The study indicated that types of complementary food provided tend to be less diverse, especially in fulfilling the required vegetable protein intake. The texture of complementary food has not been fully adjusted to the recommended age stages of children. The frequency of complementary food provision has been carried out according to established standards. For children who are not stunted, complementary feeding is generally applicable by guidelines. Complementary feeding in stunted children needs improvement in timeliness, food variety, and age-appropriate texture, although feeding frequency generally aligns with recommendations for both stunted and non-stunted children.